Performance of analysis crab leg based RF MEMS switch for defense and aerospace applications - Siddaiah, N.; Prasad, G.R.K.; Sai Pravallika, S.; Sai Prasanna, G.V.; Raja Gopal, R. (International Journal of Engineering and Technology, 2017)
In this paper the design and modeling of capacitive shunt switch for k-ka band applications is presented. The proposed model for this design is the crab leg flexure. In order to reduce the squeeze film air damping, the perforated switch with reduced spring constant is designed. Analysis of designed switch has been carried out on the various parameters of the switch such as damping factor, switching time, quality factor and Eigen frequencies in order to design a reliable switch. The results indicate that the obtained pull in voltage is 3.1V for the dielectric gap of 1mm and spring constant of 2.95N/m2. Switching time is observed as 1.2ms and 2.15ms for the gap of 1mm and 1.5mm respectively. The capacitance ratio i.e. Cdown/Cup Â is 211.11 for HfO2 and 100.741 for Si3N4. Resonant frequency is obtained as 14.45 KHz. Return loss is calculated as-44.85dB at a frequency of 1GHz and -25.68dB at a frequency of 27.5GHz and insertion loss is obtained as -0.0447db at 1GHz and -1.0379dB at 27.5GHz. The maximum peak isolation is observed as -59.5dB at 1GHz frequency and -71dB at 27.5GHz frequency.